(untitled) (International Journal of Food and Nutritional Sciences, 2019)
In this investigation, we explore the combined effects of a magnetic field, thermal radiation, buoyancy force, viscous dissipation, and chemical reaction on the flow of a Casson fluid over a permeable stretching surface. The nonlinear model equations are formulated and transformed into a set of ordinary differential equations (ODEs).